Microstructure and Phase Composition of 3D-Printed Titanium Alloy Ti-6Al-4V Parts Subjected to Thermal Post-Processing; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Evtushenko O. Oksana; Panin A. V. Alexey Viktorovich; Kazachenok M. Marina; Perevalova O. Olga; Martynov S. Sergey (2018, 2018)
Title screen